Oratory and Politics in the Sagas - Bagge, Sverre (Éditions de la Sorbonne, 2019)
Introduction The Norwegian and Icelandic kings' sagas form a prominent example of the revival of historiography in the High Middle Ages. From a literary point of view, the use of the vernacular was earlier and more widespread in Norway and Iceland in the Middle Ages than in most other countries of Europe, and the saga writers developed a very characteristic style, which is simple and terse, while at the same time aiming at maximum dramatic effect. This effect is achieved by "letting the event.